Understanding Students’ Interest in Akidah Akhlak Learning: Factors and Improvement Strategies at MTsN 4 Banda Aceh - Muhammad Abrar; Nia Nisa; Kaipal Wahyudi; Fitria Andriani (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2026)
Islamic religious education plays an important role in developing students’ faith, character, and moral behavior. In Akidah Akhlak learning, students’ interest is particularly important because learning is expected to connect religious knowledge with everyday attitudes and behavior. This study aims to examine the dimensions and factors shaping students’ interest in Akidah Akhlak learning and to identify strategies for strengthening such interest at MTsN 4 Banda Aceh. The study employed a qualitative case study design. Data were collected through classroom observations, semi-structured interviews with students and an Akidah Akhlak teacher, and documentation of learning activities. Data were analyzed through data condensation, thematic coding and categorization, data display, and conclusion drawing and verification. The findings indicate that students’ learning interest is reflected in four dimensions: enjoyment, interest, attention, and active engagement. These dimensions are shaped by several interrelated factors, including the teacher’s pedagogical approach, the relevance of learning materials, the madrasah environment, instructional and digital media, and students’ intrinsic motivation. The study also identifies six strategies for strengthening learning interest: contextual learning, interactive discussion, storytelling, role-playing, digital and visual media, and religious extracurricular activities. The findings suggest that students’ interest develops through a thematic progression from positive learning experiences toward greater attention and active engagement. Accordingly, Akidah Akhlak learning should be developed through contextual, participatory, and value-oriented approaches that connect religious knowledge with students’ everyday experiences and moral practice.